Literature Review: Hubungan Keanekaragaman Konsumsi Pangan Dengan Kejadian Diabetes Melitus - Ferdiyan, Muhammad; Kurniasari, Ratih (Peneliti.net, 2024)
Diabetes mellitus is a chronic disease characterized by high blood sugar levels above normal limits. Apart from being the cause of premature death globally, diabetes is also a major cause of blindness, kidney failure and heart disease. This research aims to explore the relationship between diet and diabetes mellitus. The method is literature analysis, in which information from previous publications is reviewed and summarized. The data used is secondary data. Of the five journals analyzed, all showed a significant relationship between diet and the risk of diabetes mellitus. Irregular eating patterns, consuming unhealthy foods, and not adhering to the principles of a balanced diet are the main factors in the occurrence of diabetes mellitus. Unbalanced nutritional intake and the habit of eating excessive portions can result in unstable blood sugar levels in the body. Therefore, maintaining a healthy, balanced and regular diet is key in preventing and managing diabetes mellitus, as well as reducing the risk of serious complications that can arise from this disease.